Upaya Peningkatan Pengetahuan Ibu Hamil Melalui Edukasi Mengenai Kebutuhan Nutrisi Ibu Hamil - Armiyati Nur; Rusnaeni Saide; Tri Utami Ramli (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
When you are pregnant, most nutritional needs will increase. It is important for pregnant women to ensure that the food they consume is balanced. The aim of this community service program is to increase pregnant women's understanding of nutrition during pregnancy. This activity was carried out on May 7 2022 through counseling using leaflets to pregnant women before and after the counseling. This counseling was carried out in Kassi - Kassi, attended by 10 pregnant women who implemented the Covid-19 Health Protocol. The results of the counseling showed an increase in understanding of 50%. Before the counseling, only 3 pregnant women (30%) had good understanding, but after this activity, the number increased to 8 pregnant women (80%) who had good understanding. We hope that in future counseling, there will be more focus on nutrition during the first, second and third trimesters of pregnant women.